Best surgical technique and outcomes for large macular holes: retrospective multicentre study in Japan. Issue 8 (19th April 2018) - Yamashita, Toshifumi; Sakamoto, Taiji; Terasaki, Hiroto; Iwasaki, Masanori; Ogushi, Yoko; Okamoto, Fumiki; Takeuchi, Masaru; Yasukawa, Tsutomu; Takamura, Yoshihiro; Ogata, Nahoko; Nakamura, Yumiko
Abstract: The purpose of this study was to compare the surgical outcomes of vitrectomy with conventional internal limiting membrane (C‐ILM) peeling to that with the inverted ILM (I‐ILM) flap technique for large macular holes (MHs). This was a retrospective chart review of consecutive cases with a large MH at nine hospitals in Japan. Among the 1342 eyes, 165 eyes of 165 cases met the inclusion criteria. The results for medium‐large MHs with a diameter 400–550  μ m were compared to that of eyes with an extra‐large MH with a diameter >550  μ m. In addition, the results of C‐ILM peeling were compared to that of the I‐ILM technique. In medium‐large MHs, the closure rate was 95.2% (59/62) by C‐ILM peeling and 100% (19/19) by the I‐ILM technique. In extra‐large MHs, the closure rate was 88.4% (38/43) by C‐ILM peeling and 100% (41/41) by I‐ILM. Although the difference between the two methods was not significant, the I‐ILM technique was successful in 100% of the cases. Multiple logistic regression analysis showed the best‐corrected visual acuity (BCVA) at 6 months was significantly associated with the preoperative BCVA, MH size, age and sex of the patient. Analyses of the eyes with extra‐large MHs show that the surgical success is high, and the I‐ILM technique is more effective for closure in eyes with extra‐large MHs.